The evaluation of stochastic mosquito-borne infectious disease mapping model in Malaysia - Syafiqah Husna Mohd Imam Maarof (N/A, 2016)
The evaluation of stochastic mosquito-borne infectious disease mapping model in Malaysia by Syafiqah Husna Mohd Imam Maarof